Literasi Matematika Siswa dalam Menyelesaikan Soal PISA Ditinjau dari Resiliensi Matematis - Ramadhani, Safira Putri; Kurniasari, Ika (MATHEdunesa, 2025)
Mathematical literacy is a person's ability to formulate, apply, and interpret mathematics in various real-world contexts. This study aims to describe the mathematical literacy of students with high, medium, and low mathematical resilience in solving PISA questions. This research is a descriptive research with a qualitative approach. The research subjects consisted of 1 subject each of high, medium, and low mathematical resilience. Data collection techniques used questionnaires, tests, and interviews. The results showed that in the process of formulating situations mathematically, the three subjects identified mathematical aspects in the problem, used mathematical symbols, made mathematical models of the problem, and mentioned mathematical concepts used. Low mathematical resilience subject mentioned the mathematical aspects in the problem incompletely and made mathematical models that were not appropriate. High and medium mathematical resilience subjects recognized the mathematical structure in the problem and mentioned limitations and assumptions in accordance with mathematical model. In the process of employing mathematical concepts, facts, procedures and reasoning, the three subjects applied strategies to find mathematical solutions to problems. All three subjects mentioned the mathematical symbols, rules and procedures used. Medium and low mathematical resilience subjects performed mathematical procedures that were not yet correct. High mathematical resilience subject reflected on mathematical arguments and explained and justified mathematical results. In the process of interpreting, applying and evaluating mathematical outcomes, high and medium mathematical resilience subjects drew conclusions according to the context of the problem and explained why the results obtained made sense or not based on the context of the problem.